2015
DOI: 10.1093/femsec/fiv069
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analyses reveal no differences in genes involved in cellulose degradation under different tillage treatments

Abstract: Incorporation of plant litter is a frequent agricultural practice to increase nutrient availability in soil, and relies heavily on the activity of cellulose-degrading microorganisms. Here we address the question of how different tillage treatments affect soil microbial communities and their cellulose-degrading potential in a long-term agricultural experiment. To identify potential differences in microbial taxonomy and functionality, we generated six soil metagenomes of conventional (CT) and reduced (RT) tillag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 48 publications
3
19
1
Order By: Relevance
“…This result indicates that the bacterial community grows in abundance, and eventually adapts and stabilizes with agricultural practices. This is in accordance with other studies showing a stable community under long‐term treatments (at least on the DNA level) (de Vries et al , ; Cania et al , ). Moreover, soil organic carbon concentrations peaked at RA6 and decreased at RA12 and RA24 (Pihlap et al , ), likely because organic fertilizers were applied only in the 4th and 7th year of the reclamation process.…”
Section: Discussionsupporting
confidence: 93%
“…This result indicates that the bacterial community grows in abundance, and eventually adapts and stabilizes with agricultural practices. This is in accordance with other studies showing a stable community under long‐term treatments (at least on the DNA level) (de Vries et al , ; Cania et al , ). Moreover, soil organic carbon concentrations peaked at RA6 and decreased at RA12 and RA24 (Pihlap et al , ), likely because organic fertilizers were applied only in the 4th and 7th year of the reclamation process.…”
Section: Discussionsupporting
confidence: 93%
“…While not measured, the no‐till fields appeared to have higher crop residue and did have marginally higher levels of organic carbon (Appendix Figure S4). High levels of Chitinophagaceae in soil has been associated with increased activity of β‐glucosidase (Bailey, Fansler, Stegen, & McCue, ), an important enzyme associated with the breakdown of cellulose; note, though, that another study (de Vries, Schöler, Ertl, Xu, & Schloter, ) did not find differences in cellulose degrading gene copy number in conventionally tilled versus no‐till soils. The higher copy number of genes associated with nitrogen fixation in no‐till soils (Figure ) may be associated with the high abundance of nitrogen‐fixing Rhizobiales .…”
Section: Discussionmentioning
confidence: 99%
“…In a comparison of conventional tillage versus reduced tillage cropping soil, tillage had no effect on the composition of GH families (de Vries et al, 2015). However, significantly higher activities of cellobiohydrolase and b-glucosidase occurred under reduced tillage, where TOC and N were greater (1.6% versus 1.1% and 0.2% versus 0.1% for C and N, respectively) after 13 years of tillage management (de Vries et al, 2015). Conversely, where TOC (%) does not change between management practices (conventional versus growth of N-fixing legumes during a fallow period) the activity of cellobiohydrolase and b-glucosidase does not change (Bossio et al, 2005).…”
Section: Extracellular Enzyme Activitymentioning
confidence: 94%
“…Similarly, a comparison of conventional cropping versus low input management of a corn-soybean-winter wheat rotational cropping soil showed that where SOC (%) was significantly lower under conventional management, there was a loss in relative abundances of functional genes involved in the degradation of starch, hemicellulose, cellulose, aromatic C compounds and an endochitinase (Xue et al, 2012). In a comparison of conventional tillage versus reduced tillage cropping soil, tillage had no effect on the composition of GH families (de Vries et al, 2015). However, significantly higher activities of cellobiohydrolase and b-glucosidase occurred under reduced tillage, where TOC and N were greater (1.6% versus 1.1% and 0.2% versus 0.1% for C and N, respectively) after 13 years of tillage management (de Vries et al, 2015).…”
Section: Extracellular Enzyme Activitymentioning
confidence: 99%
See 1 more Smart Citation